Partisipasi Partisipasi Masyarakat dalam Pengembangan Desa Wisata Hariarapohan Kecamatan Hariarapohan Kabupaten Samosir Sumatera Utara - Ika Fitria Hasibuan; Eni Sumiarsih; Sefrona Syaiful; Rahma Putri Andita; Rita Megawati Rajagukguk (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
Successful tourism development is a development that is carried out together, with the term "Building with the community" so that tourism development can provide benefits to the local community, and good management of tourist villages is one that involves community participation in it. This study aims to determine Community Participation in the Development of Hariarapohan Tourism Village, Hariarapohan District, Samosir Regency, North Sumatra. In this study using qualitative descriptive research methods of data collection through observation, distributing questionnaires, interviews, and documentation to obtain data related to the management of Tourism Villages, which are samples in the study, namely Village Officials and 100 community members. The problem in this study is the forms of community participation in Tourism Villages and the level of community participation in Tourism Villages, This study aims to analyze how the forms of community participation in Tourism Villages and how the level of community participation in Tourism Villages. The results of the study are community participation in the form of thoughts, energy, thoughts and energy, expertise, goods, money. And the results of the research show that the Hariarapohan Tourism Village community participated in the development of the Hariarapohan Tourism Village, and the level of community participation in the development of the Hariarapohan tourism village was high, so it can be concluded that the community participated in the development of the Hariarapohan Tourism Village, Hariarapohan District, Samosir Regency.